Social and psychological well-being index among Malaysians - Nur Malek, Nerisha Sarah; Mohd Yusof, Halimah; Abdull Rahman, Rabeatul Husna (Journal of Islamic, Social, Economics and Development, 2025)
Well-being is a multidimensional concept that is essential to individuals, which can be influenced by a multitude of factors including demographics. However, there are limited studies that focus on psychological and social well-being among the Malaysian demographics. The main objective of this study is to assess demographic features and psychological well-being, social well-being, and negative emotional symptoms with an instrument developed for the Malaysian context. The study recruited 382 participants from varying backgrounds including age, gender, ethnicity, number of dependants, household income, and educational level. Our overall findings presented mean differences between age and educational level for psychological well-being. While social well-being was different between gender, education, and income. Lastly, age, educational level, and income differences were demonstrated on negative emotional symptoms. Accordingly, the implications of this study may influence the government's efforts to address Malaysians' well-being disparities among different demographic groups.